Fixed Point Results for Multivalued Contractive Mappings Endowed with Graphic Structure - Tahair Rasham; Abdullah Shoaib; Badriah A. S. Alamri; Muhammad Arshad (Journal of Mathematics)
The aim of this paper is to introduce the notion of admissible multivalued mappings and to set up fixed point results for such mappings fulfilling generalized locally Ćirić type rational-contractive conditions on a closed ball in complete dislocated b-metric space. Example and application have been given to demonstrate the novelty of our results. Our results combine, extend, and infer several comparable results in the existing literature.